(untitled) (Acta Polytechnica CTU Proceedings, 2022)
A new detection device for the measurements of light ions (p, d, t, α) emitted as the products of the nuclear reactions induced by fast neutrons (5-33 MeV) was recently developed at the Nuclear Physics Institute of the Czech Academy of Sciences. The main objective of the Chamber-for-Light-Ion-Detection (CLID) is to produce new differential nuclear data of high interest for the material applications related to fusion and aerospace technologies and to potentially test and validate models of nuclear reactions. Hereby the experimental set-up for the measurements with the CLID is described in detail. The experimental characterization of the collimated fast neutron beams produced by the cyclotron-driven converter (p(35 MeV)+Be(2.5 mm)) is presented. In particular, the implementation of the Proton-Recoil-Telescope technique used for neutron energy spectra determination with the CLID is described.